Study of laser - induced plasma using two focusing techniques - Ali, Ahmad Hadi (Penerbit Universiti Tun Hussein Onn Malaysia, 2011)
Plasma plays an important role in laser fusion research. High power laser is used to drive the reaction. Hence the laser turns to become very crucial devices to form plasma. Generation of plasma can be done by various focusing techniques. Therefore the aim of this project is to determine the best focusing techniques in order to produce strong plasma. Two focusing techniques were considered, that are a single lens technique, and combination lenses technique. A high-speed photographic system was developed in conjunction with image processing system to visualize and record the plasma activities in the focused region. An electrical spark was observed at the focal region which indicates the existence of an optical breakdown. The results shown that the maximum plasma widths were obtained correspond to the peak power of 22.21 MW using a combination lenses technique in comparison to 21.93 MW for the single lens technique. In general, combination lenses technique produces more consistent plasma, although it size is small. A single lens technique induced large plasma but associated with turbulence condition as indicated by blurred image.